A Single High-Intensity Shock Wave Pulse With Microbubbles Opens the Blood-Brain Barrier in Rats - Kung, Yi; Huang, Hsin-Yu; Liao, Wei-Hao; Huang, Abel P.-H.; Hsiao, Ming-Yen; Wu, Chueh-Hung; Liu, Hao-Li; Inserra, Claude; Chen, Wen-Shiang (Frontiers in Bioengineering and Biotechnology, 2020)
Focused extracorporeal shockwave (FSW), one kind of focused high-intensity pulsed ultrasound, has been shown to induce blood-brain barrier (BBB) opening in targeted brain areas in rat animal models with minimal detrimental effects below threshold intensity levels or iterations. In the current study, we found that the thresholds could be further reduced by the addition of microbubbles (ultrasound contrast agents or UCA; SonoVue). FSW with 2 × 106 MBs/kg of UCA (20 % of clinical dosage) at an intensity level of 0.1 (peak positive pressure 5.4 MPa; peak negative pressure -4.2 MPa; energy flux density 0.03 mJ/mm2) resulting in a 100 % BBB opening rate without detectable hemorrhage or apoptosis in the brain. Significantly reduced free radical production was found compared with 0.5 MHz focused ultrasound at a peak negative pressure of 0.44 MPa (1% duty cycle and 4 × 107 MBs/kg of UCA). FSW devices offer advantages of commercial availability and high safety, and thus may facilitate future research and applications of focal BBB opening for oncological and pharmacological purposes.